Les Défis du Lien Entre Humanitaire et Développement: le Cas du “Linking Relief, Rehabilitation and Development” (Glocalism: Journal of Culture, Politics and Innovation, 2022)
The article explores the links between humanitarian action and aid to development, focusing more specifically on the model Linking Relief, Rehabilitation and Development. Taking this model as an example, the theoretical and practical challenges of this relationship are explored, including the foundational principles of both humanitarian action and aid to development. In this respect, the contradictions between the key rules of both perspectives are underlined, especially when it comes to the influence of governments on agendas, strategies, and operational options. Yet, the practice seems to show new possibilities of articulation, if not of junction, between humanitarian action and aid to development. In the light of recent experiences, including the World Humanitarian Summit, both strategies may mutually combine, in order to benefit local populations. The principle of humanitarian subsidiary is suggested as one of the potential element in this equation.
Keywords: humanitarian action; aid to development; ethics; Linking Relief Rehabilitation and Development; world humanitarian summit